The Use of Online Interactive Worksheets in Teaching Vocabulary at an Elementary School in West Jakarta (Universitas Pamulang, 2022)
The aim of this study is to examine how the implementation of online interactive worksheets can help students improve their vocabulary. This research employs a qualitative approach with a classroom action research design, following the framework by Kemmis & Taggart (1988). The study includes a pre-test administered to students prior to the implementation of the worksheets, followed by two post-tests at the end of each cycle, interviews with an English teacher, and a student questionnaire at the conclusion of the study. These methods are used to gather data and answer the research questions. The findings show that students' average pre-test score was 64.47, which increased to 72.10 in cycle 1 and further improved to 85.84 in cycle 2. Based on these results, it is evident that the use of online interactive worksheets significantly contributes to students' vocabulary improvement. Furthermore, students demonstrated a positive response throughout the learning process, indicating that they found the worksheets engaging and helpful. Vocabulary is a fundamental aspect of learning English, and these online interactive worksheets have proven to be an effective tool in helping students grasp new vocabulary. Additionally, the ease of use of these digital resources makes them an accessible and efficient medium for both teachers and students in the learning process